Ten Cate's oral histology: development, structure, and function - Nanci, Antonio (Elsevier, 2018)
Gain a deeper understanding of oral health with the definitive text in oral histology. Written by Dr. Antonio Nanci, a world-renowned leader in cell biology, the new ninth edition of Ten Cate’s Oral Histology covers all the latest research and trends in oral histology, embryology, physiology, oral biology, and postnatal growth and development that is essential to success in oral health! Considered to be the standard in the field, this renowned text uses straightforward explanations and detailed, full-color micrographs, images, and illustrations to help you better understand even the most complex topics. The back of the cover
Keywords: Mouth; histologie; zuby; ústa; zubní lékařství; Tooth